Activated Growth Factor From Platelets as Treatment for Diabetic Retinopathy Through Antioxidant-Oxidative Stress Pathway - Amin R; Hidayat R; Maritska Z; Putri TW (Diabetes, Metabolic Syndrome and Obesity)
Ramzi Amin,1,* Rachmat Hidayat,2,* Ziske Maritska,2,* Trisa Wulanda Putri1,* 1Department of Ophthalmology, Faculty of Medicine, Universitas Sriwijaya/Dr. Mohammad Hoesin General Hospital, Palembang, South Sumatera, Indonesia; 2Department of Medical Biology, Faculty of Medicine, Universitas Sriwijaya, Palembang, South Sumatera, Indonesia*These authors contributed equally to this workCorrespondence: Ramzi Amin, Department of Ophthalmology, Faculty of Medicine, Universitas Sriwijaya/Dr. Mohammad Hoesin General Hospital, Jl Dr Moh Ali KM 3.5, Palembang, South Sumatera, 30114, Indonesia, Tel +62 882 2505 3819, Email ramziamin20@gmail.comBackground: Reactive oxygen species (ROS) is known to play a significant role in the activation of chronic inflammatory processes in diabetic retinopathy. This study was aimed to evaluate activated growth factor (AGF) from platelet for diabetic retinopathy treatment, utilizing an in vivo investigation to regulate the antioxidant-oxidative stress pathway.Methods: The activated growth factor was initially derived by extracting intravenous blood from the rats. Advanced glycation end products (AGEs), p38 mitogen activated protein kinase (p38 MAPK), nuclear factor-κβ (NF-κβ), reactive oxygen species (ROS), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), superoxide dismutase (SOD) and vascular endothelial growth factor (VEGF) was assessed using enzyme linked immunoassay (ELISA). In vivo, diabetic retinopathy rat models were induced by streptozotocin injection and were evaluated by retinal funduscopy.Results: The mean diameter of the retinal artery was significantly reduced when activated growth factor with transforming growth factor-β concentration of 10 ng/mL or 100 ng/mL was administered (p< 0.05). The retinal tissue of diabetic rats showed a decline in antioxidant activity due to oxidative stress. AGF containing TGF-β (10 ng/mL and 100 ng/mL) significantly increased SOD activity (p< 0.05). AGF administration effectively decreased proinflammatory cytokines like TNF-α and IL-1β.Conclusion: The study shows that AGF, with TGF-β concentrations of 10 ng/mL and 100 ng/mL, can reduce AGEs, p38MAPK, Nf-κβ, ROS, TNF-α, IL-1β, VCAM-1, ICAM-1, and VEGF in diabetic retinopathy rats’ retinal tissue, while increasing antioxidant SOD concentration, suggesting AGF may help treat diabetic retinopathy by reducing inflammation and oxidative stress.Keywords: cytokines, inflammation, reactive oxygen species, transforming growth factor